2018
DOI: 10.1080/21691401.2018.1511574
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic peptide-based nanostructures as efficient siRNA carriers

Abstract: RNA interference shows a great strategy for biological studies; however, delivering of small interfering RNA (siRNA) remains challenging. Although several delivery vehicles, including cell-penetrating peptides, have been developed, their implementation is often restricted because of their endosomal entrapment. Herein, we report the formation of self-assembled nanostructures from rationally designed cyclic peptides and explore them for efficient delivery of functional biomacromolecules such as siRNA into mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Another approach is to modify the structure of the CPP. For example, it is possible to enhance cellular uptake by changing peptides into cyclic peptides [51,114,115], dendrimers [116], or transform their side chains [117,118,119]. Furthermore, the addition of trifluoromethylquinoline moieties [120] or replacement of certain residues with histidines are common strategies to make endosomolytic CPPs [121,122].…”
Section: Cpp-based Anti-cancer Therapy Optimizationmentioning
confidence: 99%
“…Another approach is to modify the structure of the CPP. For example, it is possible to enhance cellular uptake by changing peptides into cyclic peptides [51,114,115], dendrimers [116], or transform their side chains [117,118,119]. Furthermore, the addition of trifluoromethylquinoline moieties [120] or replacement of certain residues with histidines are common strategies to make endosomolytic CPPs [121,122].…”
Section: Cpp-based Anti-cancer Therapy Optimizationmentioning
confidence: 99%
“…However, it is important to find the delicate balance between enhanced stability to ensure the delivery of the CPP-protein molecules to the targeted cellular component and its sufficient clearance to avoid non-specific toxicity. For example, it is possible to enhance cellular uptake by changing peptides into cyclic peptides [ 29 , 116 , 117 ], dendrimers [ 118 ], or changing their side chains [ 119 , 120 , 121 ]. Addition of tri-fluoro-methyl-quinoline moieties [ 122 ] or change of certain amino acids with histidine are also utilized to enable endosome escape of CPPs [ 123 , 124 ].…”
Section: Obstacles/limitations Of Utilizing Recombinant Cpp-enzymes/proteins For Human Therapymentioning
confidence: 99%
“…For example, it is possible to enhance cellular uptake by changing peptides into cyclic peptides [ 29 , 116 , 117 ], dendrimers [ 118 ], or changing their side chains [ 119 , 120 , 121 ]. Addition of tri-fluoro-methyl-quinoline moieties [ 122 ] or change of certain amino acids with histidine are also utilized to enable endosome escape of CPPs [ 123 , 124 ].…”
Section: Obstacles/limitations Of Utilizing Recombinant Cpp-enzymes/proteins For Human Therapymentioning
confidence: 99%
“…Ample attention is also being directed to cell-penetrating peptides (CPPs), as carriers for intracellular transport cargoes such as siRNA, nucleic acids, proteins, various nano-particulate pharmaceutical carriers (e.g., liposomes, micelles), small molecule therapeutic agents as well as quantum dots and MRI contrast agents (Brasseur and Divita, 2010;Bechara and Sagan, 2013;Choi and David, 2014;Copolovici et al, 2014;Wang et al, 2014;Huang et al, 2015;Skotland et al, 2015;Dinca et al, 2016;Kurrikoff et al, 2016;Lehto et al, 2016;Guidotti et al, 2017;Hoffmann et al, 2018;Panigrahi et al, 2018;Ramaker et al, 2018;Vánová et al, 2019), since these are internalized by cells in an exceedingly effective manner. The study by Ramaker et al observed a statistically substantial dependence of CPPs' uptake efficiency on both net charge and peptide length; longer CPP possibly due to more ordered α-helical structure with high charge could ferry conjugated cargo across membranes more efficiently (Ramaker et al, 2018).…”
Section: Applications Of Peptide Self-assembliesmentioning
confidence: 99%